Territorio agricolo e cambiamenti globali - Bindi, Marco; Dibari, Camilla (Ri-Vista. Research for landscape architecture, 2015)
Economic, cultural, political, technology and environmental factors influence the agricultural system and territory. In particular, the climatic changes - in action and the changes forecast in the future above all - will be considerable repercussions on the agricultural territory and his productive capacities. It’s possible to introduce some arrangement strategies to reduce the negative impacts.